LUAS LAHAN DAN PEMENUHAN KEBUTUHAN DASAR (Kasus Rumahtangga Petani Miskin di Daerah Dataran Tinggi Kabupaten Kepahiang) - Bahrin Bahrin; Basita G Sugihen; Djoko Susanto; Pang S Asngari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The mayority of the poor farmers have relativity enough land, approximately 1 Ha per household. Their poverty is considered as relatively poor. There were four factors which make the poor farmers hardly overcome their problems, namely: working pattern which mostly rely on physical potency; low level of adoption of innovation; poverty trap bounding and low competence to manage opportunity and potency. The poor farmers have to be motivated to get involve in learning process. By doing this approach it is hoped that the farmers could change to get better, more effective dan more productive in land use.